Analisis Faktor yang Mempengaruhi Efikasi Diri Orang Tua untuk Vaksinasi Covid 19 pada Anak Usia 6-11 di SD Kabupaten Probolinggo - Nugroho, Setiyo Adi; Pratidina, Amanda Virga; Widad, Sofil; Rizqiyah, Afifatur; Hasanah, Nurul; Safitri, Rike Nur (Jurnal Keperawatan Profesional, 2022)
Children are the future human capital asset of a country, so the Covid-19 pandemic that affects children must also be a concern, including the need for vaccinations for children. The government officially started vaccinating children aged 6-11 years on December 14 with a target number of around 26.5 million children. However, the success of Covid 19 vaccination in children must refer to the success of adult vaccination. Parents have an important role in children's Covid-19 vaccines, because the decision to vaccinate children lies with the parents. For this reason, parents must have high self-efficacy so that children can get Covid 19 vaccination. For this reason, parents must have high self-efficacy so that children can get Covid 19 vaccination. The purpose of this study was to analyze the factors that influence parents' self-efficacy for Covid-19 vaccination in children aged 6-11 years. This research method is an analytical observational study with a quantitative approach. This research is a cross sectional study with a sample of 120 respondents. The sampling technique used is purpose sampling. Respondents in this study were parents in SD Probolinggo Regenc. Based on the results of the multiple linear regression test, it shows that there is a simultaneous influence between the independent variables consisting of X1 (individual belief) and X2 (attitude towards behavior) on Y (parental self-efficacy).